Diethylcarbamazine Attenuates the Development of Carrageenan-Induced Lung Injury in Mice - Edlene Lima Ribeiro; Karla Patricia de Souza Barbosa; Ingrid Tavares Fragoso; Mariana Aragão Matos Donato; Fabiana Oliveira dos Santos Gomes; Bruna Santos da Silva; Amanda Karolina Soares e Silva; Sura Wanessa Santos Rocha; Valdemiro Amaro da Silva Junior; Christina Alves Peixoto (Mediators of Inflammation)
Diethylcarbamazine (DEC) is an antifilarial drug with potent anti-inflammatory properties as a result of its interference with the metabolism of arachidonic acid. The aim of the present study was to evaluate the anti-inflammatory activity of DEC in a mouse model of acute inflammation (carrageenan-induced pleurisy). The injection of carrageenan into the pleural cavity induced the accumulation of fluid containing a large number of polymorphonuclear cells (PMNs) as well as infiltration of PMNs in lung tissues and increased production of nitrite and tumor necrosis factor-α and increased expression of interleukin-1β, cyclooxygenase (COX-2), and inducible nitric oxide synthase. Carrageenan also induced the expression of nuclear factor-κB. The oral administration of DEC (50 mg/Kg) three days prior to the carrageenan challenge led to a significant reduction in all inflammation markers. The present findings demonstrate that DEC is a potential drug for the treatment of acute lung inflammation.